Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

A unified heterogeneous implementation of numerical atomic orbitals-based real-time TDDFT within the ABACUS package - Taoni Bao; Yuanbo Li; Zichao Deng; Haotian Zhao; Denghui Lu; Yike Huang; Chao Lian; Lixin He; Mohan Chen (Computer Physics Communications, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

Molten-salt assisted synthesis of MAX@straw composites for electromagnetic absorption - Zonglin Liu; Han Li; Xu Zhao; Fuhua Xue; He Chen; Qian Yan; Haowen Zheng; Huanxin Lian; Yunxiang Chen; Teng Fei; Baiqiao Bao; Qingyu Peng; et al. (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dynamic monitoring deployment for improved key-region radiological forecasts via ensemble-based forward–adjoint information - Qingyun Li; Tao He; Mingye Li; Yu Song; Junfang Zhang; Bing Lian; Liye Liu; Rui Qiu; Junli Li; Xiaole Zhang (Journal of Hazardous Materials, 2026)

Effects of artificial biological soil crust establishment on spoil substrate structure, carbon sequestration, and bacterial community assembly on a high-altitude slope - Ruizhi He; Qi Li; Renjie Wei; Chengbo Hu; Jiahao Tang; Lian Gan; Ke Zhang; Binghe Wang; Xiangjun Pei (Journal of Environmental Management, 2026)

On-site quantification of machining aerosols via a smartphone-based carbon dot photoluminescence platform - Jiadi Lian; Xuming Huang; Hangqing Xie; Jing Xu; Tie Zhang; Dan He; Pengfei Li; Chenlin Zhu (Journal of Aerosol Science, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Histone lactylation inhibits Slc25a51 expression and thus promotes collagen dysregulation of pelvic organ prolapse through impairing mitochondrial NAD+ transport - Yong He; Cheng Liu; Bingshu Li; Shasha Hong; Jianming Tang; Guotao Huang; Lian Yang; Mao Chen; Shufei Zhang; Ya Xiao; Jianfeng Liu; Minqi Ning; et al. (Science China Life Sciences, 2026)

Single-cell sequencing reveals the co-option of epithelial structural programs by macrophages in teleost granulomas - Zhengyang Zhou; Jinlai Gu; Zhengran Jian; Jie He; Zhendong Zhong; Quanxin Xiong; Min Qi; Yuanchang Gao; Sheng Lian; Shangjie Bai; Chenwang Lu; Linfeng Kuang; et al. (Aquaculture, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Flavour changes and quality evolution of pork patties during fat reduction via modified microwave equipment - Fengli Lian; Jinbao Yang; Hongju He; Yangli Wan; Xianqing Huang; Bo Li (Food Research International, 2026)

Divergent assembly mechanisms and network stability of microeukaryotes between water column and sediment in a marginal sea - Feilong Liu; Xiaoli Zhang; Kaiyue Lian; Yi Li; Can Wang; Chuyu Zhang; Honglei Zhang; Bo Wang; Qian Liu; Hui He; Cui Guo; Andrew McMinn; et al. (Marine Pollution Bulletin, 2026)

A machine learning framework for decision support in optimizing nanofiltration processes against persistent organic pollutants - Tengyi Zhu; Zhenyu Yang; Cuicui Tao; Yi Li; Shuyin Li; Lian He; Haomiao Cheng; Bipeng Yan (Journal of Environmental Chemical Engineering, 2026)

Thermally regulated adsorption–desorption processes at the plastic–liquid interface drive microplastics release from sealed plastic bags - Yiting Lian; Dunzhu Li; Shuiyi He; Yushu Chen; Yuhui Fu; Baofeng Zhang; Chengran Fang; Hai Xiang; Huajun Feng (Journal of Environmental Chemical Engineering, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Anisotropic stimuli-responsive hydrogel enabling tunable electromagnetic interference shielding and strain sensing - Qian Yan; Han Li; Teng Fei; Zonglin Liu; He Chen; Huanxin Lian; Yunxiang Chen; Haowen Zheng; Baiqiao Bao; Xu Zhao; Liangliang Xu; Fuhua Xue; et al. (Chemical Engineering Journal, 2026)

O, S, C isotopic signatures of high-arsenic groundwater in Ngari, Xizang: Seasonal-scale drivers of arsenic release mechanisms - Lian Song; Shehong Li; Jen-How Huang; Fei He; Qiao Han; Jie Liao; Zhenjie Zhao; Ci Ren Qu Ji; Yong Shui (Acta Geochimica, 2026)

Mechanoadaptive conductive hydrogels with dual functionalities for epidermal sEMG monitoring and diabetic wound healing - Guoqiang Ren; Jingyun Ma; Qiuyue Peng; Pengfei Liu; Xiaobo Wang; Da Li; Yuesheng Zhang; Chaonan He; Chen Huang; Honghua Ye; Yavuz Nuri Ertas; Qingbo Xu; et al. (Chemical Engineering Journal, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Astrocyte–microglia IL-3–IL-3Rα signaling drives JAK2/STAT5-dependent neuroinflammation and neurodegeneration after status epilepticus - Liu Xie; Lian Liu; Xutao Wang; Xiao Wang; Bolin He; Tiantian Wang; Honghao Xu; Zhilin Li; Shuisheng Lei; Xiaoqin Zhu (Experimental Brain Research, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Achievement of broadband microwave absorption and infrared stealth in PEEK composites with a low filling ratio via a hierarchical design - Yashu He; Fengyu Wen; Yageng Bai; Yifan Wang; Jierun Ma; Haoyuan Tan; Yuxuan Gu; Pengbo Lian; Lei Li; Hailiang Yang; Jianxin Mu (Chemical Engineering Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Daily Arctic first-year sea ice thickness observed by China’s GNSS-R satellite constellation - Yuan Li; Lei Zheng; Qi Liang; Teng Li; Chuyue Peng; Lian He; Qiuyang Zhao; Zhuoqi Chen; Qi Tang; Ying Li; Beibei Liang; Shengli Wu; et al. (Science Bulletin, 2026)

Structural integrity of the teleost granuloma: a macrophage barrier driven by coordinated activation of junctional, cytoskeletal and extracellular matrix gene networks - Zhengyang Zhou; Linfeng Kuang; Chenwang Lu; Jie He; Zhengqiang Yu; Zhendong Zhong; Quanxin Xiong; Min Qi; Jinlai Gu; Yuanchang Gao; Sheng Lian; Zhengran Jian; et al. (Fish & Shellfish Immunology, 2026)

Joint inversion of 2.5-D controlled-source electromagnetic and surface to borehole electromagnetic data: case studies for mineral exploration and mineral discrimination - Jinghe Li; Lian Liu; Xing Li; Sheng He (Applied Geophysics, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

The impact of short-term exposures to PM2.5 components and the modification effects of ozone on daily mortality - Ziqi Tang; Jianhui Guo; Jinyi Zhou; Hao Yu; Yizhu Zhang; Yaqi Wang; Xinyao Lian; Jin Ye; Xueqiong He; Renqiang Han; Jing Li; Shaodan Huang (Atmospheric Environment, 2025)

Short-term effects of atmospheric oxidative capacity (Ox) on total, acute and chronic respiratory mortalities, and its modification on fine particle's effects - Ruosu Zhang; Dongxia Jiang; Zhaokun Wang; Yi Fan; Xueqiong He; Jianhui Guo; Yaqi Wang; Xinyao Lian; Ziqi Tang; Hao Yu; Renqiang Han; Jin Ye; et al. (Atmospheric Environment, 2025)

A full-scale attention-augmented CNN-transformer model for segmentation of oropharyngeal mucosa organs-at-risk in radiotherapy - Lian He; Jianda Sun; Shanfu Lu; Jingyang Li; Xiaoqing Wang; Ziye Yan; Jian Guan (Physical and Engineering Sciences in Medicine, 2025)

Population pharmacokinetic characteristics of tacrolimus in Chinese lung transplant recipients and optimisation of dosing regimen during the early post-transplantation phase - Shouning Zhou; Qiaoyan Lian; Huilong Luo; Hui Xie; Yanping Guan; Jianxing He; Li Wei; Chunrong Ju (European Journal of Clinical Pharmacology, 2025)

Decoding the Chemodiversity blueprint: Chromosome-scale genome assembly unveils photosynthesis-terpenoid coordination in Cinnamomum burmanni through genomic and miRNA regulatory networks - Chen Hou; Yanling Cai; Jun Yao; Peiwu Xie; Boxiang He; Huimign Lian; Yingli Wang; Yonglin Zhong; Bing Li; Minghuai Wang; Qian Zhang (Plant Science, 2025)

Embryonic exposure to nanoplastics affects the metabolism and locomotor performance of a soil-dwelling, oviparous skink - Xinni He; Jiahui Xu; Shufang Zhang; Mengzhen Hu; Congcong Wang; Miao Guan; Peng Li; Lian Chen; Longhui Lin; Georgia Ward-Fear; Hong Li (Environmental Pollution, 2025)

Modification of oceanic lithospheric mantle by percolated melts sourced from recycled ancient crust: Evidence from Ca Os isotopes of refractory harzburgites - Hui-Chao Rui; Olivier Namur; Dong-Yang Lian; Peng-Jie Cai; Jie Li; Yurisley Valdes-Mariño; Jing-Sui Yang; Hong-Ping He (Chemical Geology, 2025)

Study on multi-dimensional dynamic changes and quality control of Aurantii Fructus during the stir-frying with bran process - Lele Gao; Liang Zhong; Tingting Feng; Mengyu Zhang; Jianan Yue; Difan Wang; Kechun Liu; Qiuxia He; Shouyao Huang; Chunguo Yang; Lian Li; Lei Nie; et al. (Food Research International, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

ZmDof08, a zinc finger transcription factor, plays critical roles in photosynthesis in maize - Ting Li; Jinjie Guo; Jiahao Zhang; Ping Deng; Yuanyuan Xu; Xinjia Li; Yu He; Lian Zhou; Chaofeng Li; Chaoxian Liu (Plant Cell Reports, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Outbreaks of Ulva prolifera green tides reduce the network complexity and stability of cooccurring planktonic microbial communities - Honglei Zhang; Hui He; Feilong Liu; Can Wang; Kaiyue Lian; Chuyu Zhang; Yi Li; Bo Wang; Andrew McMinn; Hualong Wang; Min Wang (Journal of Environmental Sciences, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

Insights into the potential enhanced cadmium toxicity in marine fish Centroprostis striata in the context of global warming - Qing Ji; Xingqiang Wang; Anxin Shi; Mei Cao; Jie Lian; Jingchao He; Honglu Guo; Xiangyuan Li; Ziyi Zhang; Jiachen Yu; Jiansheng Ye (Marine Pollution Bulletin, 2025)

Ecological risks of cadmium-contaminated non-prey food on three Trichogramma egg parasitoids - Jie Wang; He-Xi Huang; John T. Trumble; Chengxing Wang; Zheng-Yang Zhu; Lian-Sheng Zang; Nicolas Desneux; Ning Di; Yuan-Xi Li (Journal of Pest Science, 2025)

Experimental investigation of 15.5-m prototype segment lining structures: The load equivalent method and in-situ verification - Li Zhang; Zhengzhou Lian; Kun Feng; Ruoyang Tang; Chuan He (Tunnelling and Underground Space Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Electronic-ionic dual-conductive framework/channel stabilized Zn anodes for high-performance aqueous Zn-ion batteries - Qian He; Zekai Zhang; Hongchun Mu; Cheng Lian; Quan Li; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

The unnoticed risk: Chronic nitrite exposure disturbs the intestinal barrier, new insights from juvenile starry flounder (Platichthys stellatus) - Jie Lian; Jingchao He; Honglu Guo; Anxin Shi; Xiangyuan Li; Qing Ji; Ziyi Zhang; Xingqiang Wang; Suyue Zhou; Bo Qin; Jiachen Yu (Aquaculture, 2025)

Full-scale shaking table test on a precast sandwich wall panel structure with a high-damping viscoelastic isolation and mitigation device - Zhong-Wei Hu; Zhao-Dong Xu; Lian-Yu Zhang; Jia-Xuan He; Zheng-Han Chen; Qi-Song Miao; Wen-Feng Li (Engineering Structures, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

Complete genome sequence of Sulfitobacter pontiacus WPMT18310, a dimethylsulfoniopropionate (DMSP) degradation bacterium isolated from the Mariana Trench - Zeping He; Lian Yuan; Haoran Li; Lihua Peng; Xiao Liang; Jin-Long Yang (Marine Genomics, 2025)

Perennial rice regrowth responds to stubble characteristics, temperature and genotype - Guangfu Huang; Mi He; Silai Wang; Yufu Li; Jianli Li; Yujiao Zhang; Shilai Zhang; Xiaoping Lian; Jing Zhang; Len J. Wade; Fengyi Hu (Field Crops Research, 2025)

Homogeneous synthesis of cationic celluloses with broad-spectrum antibacterial activities for the treatment of vaginitis in mice - Lian Yang; Lujie Wang; Zihui Zhang; Shufei Zhang; Yong He; Ying Wang; Bingshu Li; Jinping Zhou; Li Hong (Carbohydrate Polymers, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Designed tumor microenvironment-remodeling bispolyphenol nanoparticles combined with αPD-L1 for enhanced melanoma immunotherapy - Yanzhu Wang; Linghe Zang; Liyuan Guan; Xihang Ren; Zongmin Xia; Zhou Li; Zhaoxu Meng; He Lian (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Kinetic modeling of sulfonamide degradation by UV/H2O2: Deduction of ROH,UV modeling and application - Xinxin Qin; Xinyue Liu; Yi He; Yichun Zhu; Zuwen Liu; Wentao Li; Mengkai Li; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Genetic diversity analysis of Saccharosydne procerus in Hunan region, China - Lian Shan; Yu Wu; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Lin Qiu; Youzhi Li (Molecular Biology Reports, 2024)

Desertibaculum subflavum gen. nov., sp. nov., a novel member of the family Sneathiellaceae isolated from the Kumtag Desert soil - Chu-Ying Feng; Huan-Huan He; Shuai Li; Zhuo-Huan Zheng; Yi-Jun Mo; Wen-Hui Lian; Chun-Yan Lu; Dong-Ya Zhang; Wen-Jun Li; Lei Dong (Antonie van Leeuwenhoek, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Transcriptome mechanisms of dandelion under stress of polystyrene and dibutyl phthalate and quantitative tracing of nanoplastics - Xingfan Li; Xinyi Du; Zhiqiang He; Ranran Zhou; Yang Guo; Jia Liu; Jiapan Lian; Xiaorui Guo; Zhonghua Tang (Science of The Total Environment, 2024)

Anchored Ru nanoclusters strategy enhances hydrogen spillover effect for high-efficiency hydrogen storage - Xiao-Qi Zhang; Yi-Qiang Qi; He Liu; Jun-Yu Wang; Li-Ying Xie; Jun-Lian Shi; Feng Wang; Yue-Liang Liu; Zong-Xian Wang; Ai-Jun Guo (Chemical Engineering Journal, 2024)

In-situ assembly of polypyrrole onto heterocyclic aramid for high-strength, ultratough, durable, and multifunctional films - Jinhua Xiong; Xu Zhao; Pengyang Li; Huanxin Lian; Qian Yan; He Chen; Zonglin Liu; Zhong Chen; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

Multi-constraint improved RS path planning method for unmanned rice direct seeding machine - Lian Hu; Kang Hou; Jie He; Zhongxian Man; Jiasheng Xie; Pei Wang; Tuanpeng Tu; Ruitao Gao; Le Zi; Yufeng Huang; Mingjin Li; Shuaiqi Ding; et al. (Computers and Electronics in Agriculture, 2024)

The photosynthetic toxicity of nano-polystyrene to Microcystis aeruginosa is influenced by surface modification and light intensity - Kui Xu; Libin Zhao; Philippe Juneau; Zhen Chen; Xiafei Zheng; Yingli Lian; Weizhi Li; Peihuan Huang; Qingyun Yan; Xiongwen Chen; Zhili He (Environmental Pollution, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Differences in the dynamic behavior of Cd2+ on different clay mineral (001) surfaces under the effect of electric field - Ke Yan; Zhaoyun Chai; Tianyu Li; Chang Xiao; Jian Li; Keqin Lian; Lixia He (Applied Clay Science, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Nanoplastic pollution changes the intestinal microbiome but not the morphology or behavior of a freshwater turtle - Shuo Gao; Shufang Zhang; Jiahui Sun; Xinni He; Shaoshuai Xue; Wenyi Zhang; Peng Li; Longhui Lin; Yanfu Qu; Georgia Ward-Fear; Lian Chen; Hong Li (Science of The Total Environment, 2024)

Toxicology assessment of deep-sea mining impacts on Gigantidas platifrons: A comparative in situ and laboratory metal exposure study - Li Zhou; Chao Lian; Yameng He; Xupeng Chi; Hao Chen; Zhaoshan Zhong; Minxiao Wang; Lei Cao; Hao Wang; Huan Zhang; Chaolun Li (Science of The Total Environment, 2024)

Integrated transcriptomic and metabolomic approaches reveal molecular response and potential biomarkers of the deep-sea mussel Gigantidas platifrons to copper exposure - Yameng He; Li Zhou; Minxiao Wang; Zhaoshan Zhong; Hao Chen; Chao Lian; Huan Zhang; Hao Wang; Lei Cao; Chaolun Li (Journal of Hazardous Materials, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Parental material and climate jointly determine the biomass and diversity of soil microbial communities along an elevational gradient on a subtropical karst mountain - Xianjin He; Lian Zeng; Guangyu Zhu; M. D. Farnon Ellwood; Lihua Zhou; Junlong Huang; Chenchen Wang; Wei Li; Dunmei Lin; Pei Wei; Shijun Liu; Min Luo; et al. (Journal of Biogeography, 2024)
Aim Climate is widely understood to determine elevational patterns of soil microbial communities, whereas the effects of parental material are uncertain. Changes in the composition of parental materials along elevational transects could also affect soil microbial communities by influencing soil pH and nutrient availability. Here, we aim to illustrate the combined effects of climate and parental material on the biomass and composition of soil microbial communities along an elevational transect. Location A subtropical forest on a karst mountain (Mt. Jinfo), China. Taxon Bacteria and Fungi. Methods We use phospholipid fatty acid analysis (PLFA) and DNA amplicon high‐throughput sequencing to determine biomass and diversity patterns of soil microbial communities along a subtropical elevational gradient with contrasting parental materials (limestone and clasolite). Results We observed that the microbial communities were more diverse (α‐diversity) and productive (biomass) on limestone than on clasolite. Additionally, we found that parental material played a role in shaping the composition (β‐diversity) of soil microbial communities along the elevational gradient. The impact of climate on soil microbial communities was found to be significant, albeit relatively weak. Structural equation models provided evidence for both direct and indirect effects of climate and parental material on microbial biomass and α‐diversity along the elevational gradient. Notably, the changes in soil pH, influenced by both parental material and climate, were identified as a key factor driving these effects. Main Conclusions Our results underline the importance of both climate and parental material variations in space‐for‐time studies investigating soil microbial communities along elevational gradients.

Recovery of nutrients from fish sludge to enhance the growth of microalga Chlorella sorokiniana CMBB276 - Jie Lian; Yuqing He; Lan Wang; Yang Liu; Kui Wang; Jan Sunde; Céline Rebours; Haokun Liu; Xiaoming Zhu; Danxiang Han; Qiang Hu; Meng Li (Marine Pollution Bulletin, 2024)

Construction of a physiologically based pharmacokinetic model of paclobutrazol and exposure estimation in the human body - Xiaomeng Li; Tingting Lian; Buda Su; Hui Liu; Yuming Wang; Xiaoyan Wu; Junjie He; Yue Wang; Yanyan Xu; Shenshen Yang; Yubo Li (Toxicology, 2024)

Toward soil carbon storage: The influence of parent material and vegetation on profile-scale microbial community structure and necromass accumulation - Yu-Zhu Li; Xue-Lian Bao; Shi-Xin Tang; Ke-Qing Xiao; Cheng-Jun Ge; Hong-Tu Xie; Hong-Bo He; Carsten W. Mueller; Chao Liang (Soil Biology and Biochemistry, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Host specificity of plant‐associated bacteria is negatively associated with genome size and host abundance along a latitudinal gradient - Zihui Wang; Geneviève Lajoie; Yuan Jiang; Minhua Zhang; Chengjin Chu; Yongfa Chen; Shuai Fang; Guangze Jin; Mingxi Jiang; Juyu Lian; Yanpeng Li; Yu Liu; et al. (Ecology Letters, 2024)
Host specialization plays a critical role in the ecology and evolution of plant–microbe symbiosis. Theory predicts that host specialization is associated with microbial genome streamlining and is influenced by the abundance of host species, both of which can vary across latitudes, leading to a latitudinal gradient in host specificity. Here, we quantified the host specificity and composition of plant–bacteria symbioses on leaves across 329 tree species spanning a latitudinal gradient. Our analysis revealed a predominance of host‐specialized leaf bacteria. The degree of host specificity was negatively correlated with bacterial genome size and the local abundance of host plants. Additionally, we found an increased host specificity at lower latitudes, aligning with the high prevalence of small bacterial genomes and rare host species in the tropics. These findings underscore the importance of genome streamlining and host abundance in the evolution of host specificity in plant‐associated bacteria along the latitudinal gradient.

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Quenching residual H2O2 from UV/H2O2 with granular activated carbon: A significant impact of bicarbonate - Jinfeng Zeng; Miao Zhang; Xinxin Qin; Yi He; Xinyue Liu; Yichun Zhu; Zuwen Liu; Wentao Li; Huiyu Dong; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Occurrence, removal efficiency, and emission of antibiotics in the sewage treatment plants of a low-urbanized basin in China and their impact on the receiving water - Yun Li; Jing Wang; Chunye Lin; Maoshan Lian; Mengchang He; Xitao Liu; Wei Ouyang (Science of The Total Environment, 2024)

Photocatalytic degradation of persistent antibiotic pollutants by MOF-derived bird-nest ferric molybdate - Lian Li; Mengying Xu; Yichao Deng; Jingyan Zheng; Chun He; Pier-Luc Tremblay; Tian Zhang (Journal of Water Process Engineering, 2024)

Hematite as a natural mineral in activating persulfate to degrade chlorinated compounds: combined effects of soluble iron release and surface activation - Yan Li; Lian Zhou; Juntao Zhang; Yake Wang; Guansheng Liu; Jingping He; Hua Zhong (Journal of Environmental Chemical Engineering, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

One-pot synthesis of interfacially bonded Bi4O5Br2/Bi2S3 Z-scheme heterostructures with boosted photocatalysis towards dodecylbenzenesulfonate and real hotel laundry wastewater - Wenqian Lian; Lei Wang; Lin Xu; Xiaofei Fu; Zuming He; Junwu Tao; Yongmei Xia; Huimin Li; Xinyue Xu (Chemosphere, 2024)

Rapid anammox startup in response to nitrogen loading variations: Reactor performance, microbial dynamics and mechanism exploration - Miao Zhang; Biao Li; Zhongkuo Guan; Yajun Fan; Lian He; Jun Wu (Journal of Water Process Engineering, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

Eco-friendly management of Meloidogyne incognita in cadmium-contaminated soil by using nematophagous fungus Purpureocillium lavendulum YMF1.683: Efficacy and mechanism - Xin Li; Lian-Ming Liang; Zhi-Bin Hua; Xin-Kui Zhou; Ying Huang; Jin-Hua Zhou; Yi Cao; Jian-Jin Liu; Tong Liu; Ming-He Mo (Environmental Research, 2024)

Integrating the confinement effect and bimetallic cycles in a hierarchical Co3O4@Co3O4/Fe3O4 yolk-shell nanoreactor for peroxymonosulfate activation enhancement - Bo Li; Huan-Yan Xu; Gu-Hao-Nan Chi; Li-Min Dong; Lian-Wei Shan; Li-Guo Jin; Yan-Li Zhuang; Mao-Chang Cao; Xiu-Lan He; Shu-Yan Qi (Chemical Engineering Journal, 2024)

Angelica dahurica extract and its effective component bergapten alleviated hepatic fibrosis by activating FXR signaling pathway - Chong Gao; Zhong-He Hu; Zhen-Yu Cui; Yu-Chen Jiang; Jia-Yi Dou; Zhao-Xu Li; Li-Hua Lian; Ji-Xing Nan; Yan-Ling Wu (Journal of Natural Medicines, 2024)

An improved constrained velocity inversion algorithm for geological structures - Jing-Xuan Xiong; Zhen-Hua He; Le Li; Guamg-Ming He; Hong Liu; Lian-Jun Li; Guang-Yin Wang; En-Jia Zhang (Applied Geophysics, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

High-efficiency solar-driven water purification enhanced by the in-plane temperature gradient and hydrated ions - Renjie Ding; Jinhua Xiong; Qian Yan; Pengyang Li; Xu Zhao; Zhong Chen; Zonglin Liu; Huanxin Lian; Zhigong Tang; Shanyi Du; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

Changes in bacterial community structure and carbon metabolism in sandy soil under the long-term application of chitin-rich organic material and attapulgite - He Zhang; Aurore Degré; Caroline De Clerck; Shuangshuang Li; Jinshan Lian; Yuanyuan Peng; Tao Sun; Lindan Luo; Yanan Yue; Guihua Li; Jianfeng Zhang (Applied Soil Ecology, 2024)

Investigating the diurnal effects of on-street population and streetscape physical environment on street theft crime: A machine learning and negative binomial regression approach using street view images - Han Yue; Lin Liu; Chong Xu; Guangwen Song; Jianguo Chen; Li He; Lian Duan (Applied Geography, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Synergism of nitrogen removal and greenhouse gases emission reduction in pyrite/biochar-based bioretention system coupled with microbial fuel cell: Performance and mechanism - Yunqing Li; Yinghui Tang; Qiong Wu; Yang He; Zhen Liu; Shaochun Yuan; Qiming Cheng; Xiaoke Lian; Yuqing Tan; Yihong Su; Yao Chen (Journal of Cleaner Production, 2024)

The impact of short-term exposures to ambient NO2, O3, and their combined oxidative potential on daily mortality - Ziqi Tang; Jianhui Guo; Jinyi Zhou; Hao Yu; Yaqi Wang; Xinyao Lian; Jin Ye; Xueqiong He; Renqiang Han; Jing Li; Shaodan Huang (Environmental Research, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Advanced treatment and Resource recovery of brewery wastewater by Co-cultivation of filamentous microalga Tribonema aequale and autochthonous Bacteria - Hang Su; Kui Wang; Jie Lian; Lan Wang; Yuqing He; Meng Li; Danxiang Han; Qiang Hu (Journal of Environmental Management, 2023)

Kinetic study of hydrogen abstraction reactions from n-propyl/n-butylcyclohexane by hydrogen atom - Liuchao Lian; Yunrui He; Lili Xing; Cheng Xie; Zhandong Wang; Xuetao Wang; Haojie Li (Fuel, 2023)

Exosomal circCNOT6L Regulates Astrocyte Apoptotic Signals Induced by Hypoxia Exposure Through miR99a-5p/SERPINE1 and Alleviates Ischemic Stroke Injury - Wanting He; Lian Gu; Jialei Yang; Ruirui Zhang; Jianxiong Long; Wenyi Peng; Baoyun Liang; Lulu Zhu; Miao Lv; Aruo Nan; Li Su (Molecular Neurobiology, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Rb-Sr isotopes record complex thermal modification of Chang’e-5 lunar soils - Yiheng Li; Zaicong Wang; Wen Zhang; Lian Zhou; Keqing Zong; Lanping Feng; Jiawei Li; Qi He; Zhenbing She; Xiang Wu; Zhaochu Hu; Long Xiao; et al. (Science Bulletin, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Constructing electrochemical sensor using molecular-imprinted polysaccharide for rapid identification and determination of l-tryptophan in diet - Yan-Jun Li; Li-Li Yang; Li Ni; Jia-Min Xiong; Jia-Yuan He; Lian-Di Zhou; Ling Luo; Qi-Hui Zhang; Chun-Su Yuan (Food Chemistry, 2023)

Chitin-based hydrogel loaded with bFGF and SDF-1 for inducing endogenous mesenchymal stem cells homing to improve stress urinary incontinence - Lian Yang; Fang Xie; Yang Li; Yiwen Lu; Bingshu Li; Shasha Hong; Jianming Tang; Jianfeng Liu; Jianhong Cheng; Yong He; Zihui Zhang; Shufei Zhang; et al. (Carbohydrate Polymers, 2023)

Perturbation indicator for Hall effect thruster operating state based on statistical characteristics of breathing oscillation time scale signals - Jingjing Li; Liqiu Wei; Yanlin Hu; Huibin Lian; Liwei Zhou; Xingyu Liu; Tianyuan Ji; Liang Han; Yongfeng He; Hong Li; Yongjie Ding (Advances in Space Research, 2023)

Monitoring and spatial traceability of river water quality using Sentinel-2 satellite images - Yingyin Zhang; Xianqiang He; Gang Lian; Yan Bai; Ying Yang; Fang Gong; Difeng Wang; Zili Zhang; Teng Li; Xuchen Jin (Science of The Total Environment, 2023)

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

A novel design idea of high-stability silicon anodes for lithium-ion batteries: Building in-situ “high-speed channels” while reserving space - Zhongyu He; Li Liu; Shengnan Liu; Yang Chen; Lian Sun; Chang Liu; Yanchao Zhu; Xiaofeng Wang (Chemical Engineering Journal, 2023)

Insufficient desorption of ions in constant-current membrane capacitive deionization (MCDI): Problems and solutions - Zhizhao He; Yingnan Li; Yuan Wang; Christopher J. Miller; John Fletcher; Boyue Lian; T. David Waite (Water Research, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Chemical constituents from Chloranthus henryi Hemsl. (Chloranthaceae) and their chemotaxonomic significance - Fang-You Chen; Meng-Li He; Lian-Lian Xu; Bao Yang; Yong-Ming Luo (Biochemical Systematics and Ecology, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Study on penetration resistance for thin-walled bucket foundation in muddy clay - Jijian Lian; Xinyi Li; Zhaolin Jia; Hao Zhao; Nan Shao; Zhichuan Wu; Shuaiqi He; Han Wu; Xiaoxu Zhang (Ocean Engineering, 2023)

Riverine antibiotic occurrence and potential ecological risks in a low-urbanized and rural basin of the middle Yangtze River: Socioeconomic, land use, and seasonal effects - Yun Li; Jing Wang; Chunye Lin; Maoshan Lian; Aihua Wang; Mengchang He; Xitao Liu; Wei Ouyang (Environmental Research, 2023)

A novel cerium organic network modified graphene oxide prepared multifunctional waterborne epoxy-based coating with excellent mechanical and passive/active anti-corrosion properties - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Pan Liu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2023)

Mechanisms of carbonate precipitation induced by two model bacteria - Xiaofang Li; Xiaodan He; Kaiyan Ren; Hailiang Dong; Bin Lian (Chemical Geology, 2023)

Evolutionary origin and establishment of a dioecious diploid‐tetraploid complex - Li He; Fei‐Yi Guo; Xin‐Jie Cai; Hong‐Pu Chen; Chun‐Lan Lian; Yuan Wang; Ce Shang; Yue Zhang; Natascha Dorothea Wagner; Zhi‐Xiang Zhang; Elvira Hörandl; Xiao‐Ru Wang (Molecular Ecology, 2023)
Polyploids recurrently emerge in angiosperms, but most polyploids are likely to go extinct before establishment due to minority cytotype exclusion, which may be specifically a constraint for dioecious plants. Here we test the hypothesis that a stable sex‐determination system and spatial/ecological isolation facilitate the establishment of dioecious polyploids. We determined the ploidy levels of 351 individuals from 28 populations of the dioecious species Salix polyclona , and resequenced 190 individuals of S . polyclona and related taxa for genomic diversity analyses. The ploidy survey revealed a frequency 52% of tetraploids in S . polyclona , and genomic k ‐mer spectra analyses suggested an autopolyploid origin for them. Comparisons of diploid male and female genomes identified a female heterogametic sex‐determining factor on chromosome 15, which probably also acts in the dioecious tetraploids. Phylogenetic analyses revealed two diploid clades and a separate clade/grade of tetraploids with a distinct geographic distribution confined to western and central China, where complex mountain systems create higher levels of environmental heterogeneity. Fossil‐calibrated phylogenies showed that the polyploids emerged during 7.6–2.3 million years ago, and population demographic histories largely matched the geological and climatic history of the region. Our results suggest that inheritance of the sex‐determining system from the diploid progenitor as intrinsic factor and spatial isolation as extrinsic factor may have facilitated the preservation and establishment of polyploid dioecious populations.

Methods and experiments for collecting information and constructing models of bottom-layer contours in paddy fields - Tuanpeng Tu; Jie He; Xiwen Luo; Lian Hu; Pei Wang; Gaolong Chen; Li Tian; Dawen Feng; Zhimin Wang; Zhongxian Man; Weicong Li; Zhenghui Wei; et al. (Computers and Electronics in Agriculture, 2023)

Investigating urban heat-related health risks based on local climate zones: A case study of Changzhou in China - Lei Ma; Guoan Huang; Brian Alan Johnson; Zhenjie Chen; Manchun Li; Ziyun Yan; Wenfeng Zhan; Heng Lu; Weiqiang He; Dongjie Lian (Sustainable Cities and Society, 2023)

Recognition of typical environmental control behavior patterns of indoor occupants based on temporal series association analysis - Xiangchao Lian; Han Zhu; Xinmin Zhang; Yujia Jin; Huiwen Zhou; Bin He; Zhengrong Li (Building and Environment, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Attributable risk and economic burden of pneumonia among older adults admitted to hospital due to short-term exposure to airborne particulate matter: a time-stratified case-crossover study from China - Chengwei Lin; Wanyanhan Jiang; Xi Gao; Yi He; Jia Li; Chengchao Zhou; Lian Yang (Environmental Science and Pollution Research, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Recovery of nutrients from aquaculture wastewater: Effects of light quality on the growth, biochemical composition, and nutrient removal of Chlorella sorokiniana - Yuqing He; Jie Lian; Lan Wang; Lu Tan; Fahad Khan; Yanhua Li; Hongxia Wang; Céline Rebours; Danxiang Han; Qiang Hu (Algal Research, 2023)

A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Boron isotope geochemistry of Bangor Co Salt Lake (central Tibet): implications for boron origin and uneven mixing of lake water - Bin-Kai Li; Mao-Yong He; Hai-Zhou Ma; Huai-De Cheng; Lian-Min Ji (Acta Geochimica, 2022)

Effectively compound the heterojunction formed by flower-like Bi2S3 and g-C3N4 to enhance photocatalytic activity - Yunmeng Cao; Lin Yue; Zhuang He; Zaixing Li; Jing Lian; Shilei Zhou; Xiao Luo (Environmental Science and Pollution Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Phytoremediation of soil co-contaminated with heavy metals (HMs) and tetracyclines: effect of the co-contamination and HM bioavailability analysis - Weigang Zhu; Deyuan Zhu; Jimei He; Xinxin Lian; Zhuobin Chang; Ruichao Guo; Xuhui Li; Yulong Wang (Journal of Soils and Sediments, 2022)

Nano-Molybdenum and Macleaya cordata Extracts Improved Antioxidant Capacity of Grazing Nanjiang Brown Goats on Copper and Cadmium-Contaminated Prairies - Yuanfeng Li; Jian He; Qionglian Zhang; Lian Li; Yachao Wang (Biological Trace Element Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Nocardioides acrostichi sp. nov., a novel endophytic actinobacterium isolated from leaf of Acrostichum aureum - Xiao-Hui Chen; Fei Li; Fei-Na Li; Ming-Sheng Chen; Xiao-Rui Yan; Zi-Bang He; Shun-Lian Li; You-Lang Wu; Li Tuo (Antonie van Leeuwenhoek, 2021)

Photosynthetic properties and biochemical metabolism of Cucurbita moschata genotypes following infection with powdery mildew - Bi-Hua Chen; Wei-Li Guo; He-Lian Yang; Qing-Fei Li; Jun-Guo Zhou; Xin-Zheng Li (Journal of Plant Pathology, 2020)
Powdery mildew (PM) is one of the most important fungal diseases in Cucurbita moschata (pumpkin) cultivation. This experiment was conducted to shed light on the physiological mechanisms of PM resistance in pumpkin cultivars. PM pathogen was inoculated on pumpkin seedlings, PM-susceptible genotype (JJJD) and PM-resistant genotype (inbred line 112–2) to study the PM-fungal growth, plant photosynthetic and biochemical parameters with different intervals of time. The disease index and pathogen growth observed for the PM-infected 112–2 seedlings were milder than those observed for the JJJD seedlings. The net photosynthetic rate (Pn), stomatal conductance (gs) and transpiration rate (Tr) were reduced for both the PM-infected genotypes, while the internal CO 2 concentration (Ci) increased in comparison with the non-infected controls. PM pathogen inoculation impaired the photosynthetic performance in seedlings of both genotypes and this was largely associated with stomatal closure. In comparison with the non-infected controls, the superoxide dismutase (SOD) and β-1,3-glucanase activities were reduced for both the PM-infected genotypes, while the peroxidase (POD) and phenylalanine ammonia lyase (PAL) activities were increased. The catalase (CAT) activity was reduced in the 112–2 genotype and increased in the JJJD genotype after PM pathogen inoculation. Together, our data show that PM resistance in pumpkin seedlings is associated with the maintenance of photosynthetic performance and the regulation of defense-related enzyme activities .

Comparative analysis of the gut microbiota of Apis cerana in Yunnan using high-throughput sequencing - Zhi-Wen Luo; Zhi-Xiang Dong; Yi-Fei Chen; Huan-Yuan Li; Qi-He Tang; Ji-Lian Li; Jun Guo (Archives of Microbiology, 2020)

Protein extraction and database construction in tea rhizosphere soil - Hai-bin Wang; Chun-lian Zhu; Yu-hua Wang; Qing-xu Zhang; Peng Wang; Ding Li; Xiao-li Jia; Jiang-hua Ye; Hai-bin He (Acta Physiologiae Plantarum, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Comparative transcriptomic analysis of resistant and susceptible tea cultivars in response to Empoasca onukii (Matsuda) damage - Shan Jin; Qianqian Ren; Lingli Lian; Xiaoming Cai; Lei Bian; Zongxiu Luo; Zhaoqun Li; Naixing Ye; Rifeng Wei; Weiyi He; Wei Liu; Zongmao Chen (Planta, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

Methods of extraction, separation, purification, structural characterization for polysaccharides from aquatic animals and their major pharmacological activities - Qingping Xiong; Zhuoyue Song; Weihui Hu; Jian Liang; Yi Jing; Lian He; Song Huang; Xiaoli Wang; Shaozhen Hou; Tingting Xu; Jing Chen; Danyan Zhang; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Anti-bacterial chromones from cultures of the endophytic fungus Bipolaris eleusines - Juan He; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

miR-135a deficiency inhibits the AR42J cells damage in cerulein-induced acute pancreatitis through targeting FAM129A - Kai-Kai Zhang; Shan-Shan Yu; Gui-Yun Li; Lian He; Xian-Quan Liang (Pflügers Archiv - European Journal of Physiology, 2019)

Vibralactone Z 4 , the first chain-like vibralactone derivative from cultures of the basidiomycete Boreostereum vibrans - Juan He; Kai-Ting Duan; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Physiological adaptations of Elymus dahuricus to high altitude on the Qinghai–Tibetan Plateau - Guowen Cui; Guoxu Ji; Shengyong Liu; Bing Li; Lu Lian; Wenhua He; Pan Zhang (Acta Physiologiae Plantarum, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Laboratory tests and numerical simulations on the impact of subsurface barriers to saltwater intrusion - Fu-lin Li; Xue-qun Chen; Cai-hong Liu; Yan-qing Lian; Li He (Natural Hazards, 2018)

Kinsenoside and polysaccharide production by rhizome culture of Anoectochilus roxburghii in continuous immersion bioreactor systems - Mei-Yu Jin; Lu Han; He Li; Hong-Qiu Wang; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Structural evolution and late Carboniferous magmatism of the Zhongguai arc in the western Junggar Basin, Northwest China: implications for tectonic evolution of the Junggar Ocean - Di Li; Dengfa He; Yichi Lian; Yu Lu; Zejun Yi (International Geology Review, 2017)

Effects of salinity on simultaneous reduction of perchlorate and nitrate in a methane-based membrane biofilm reactor - Yin Zhang; Jia-Xian Chen; Li-Lian Wen; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Nuclear genetic variation of Rosa odorata var. gigantea (Rosaceae): population structure and conservation implications - Jing Meng; Shui-Lian He; De-Zhu Li; Ting-Shuang Yi (Tree Genetics & Genomes, 2016)

Effect of several physicochemical factors on callus biomass and bioactive compound accumulation of R. sachalinensis bioreactor culture - He Li; Xuan Chun Piao; Ri Gao; MeiYu Jin; Jun Jiang; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2016)

Chitooligosaccharide Inhibits Scar Formation and Enhances Functional Recovery in a Mouse Model of Sciatic Nerve Injury - Hongping Hou; Lihai Zhang; Zuguang Ye; Jianrong Li; Zijian Lian; Chao Chen; Rong He; Bo Peng; Qihua Xu; Guangping Zhang; Wenbiao Gan; Peifu Tang (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Diffusible signal factor family signals provide a fitness advantage to Xanthomonas campestris pv. campestris in interspecies competition - Yinyue Deng; Jien Wu; Wenfang Yin; Peng Li; Jianuan Zhou; Shaohua Chen; Fei He; Jun Cai; Lian‐Hui Zhang (Environmental Microbiology, 2016)
Summary Diffusible signal factor (DSF) represents a new class of widely conserved quorum sensing signals, which regulates various biological functions through intra‐ or interspecies signaling. The previous studies identified that there is an antagonistic interaction between Xanthomonas and Bacillus species bacteria in natural ecosystem, but the detailed molecular mechanism of interspecies competition is not clear. This study showed that Xanthomonas campestris pv. campestris ( Xcc ) interfered with morphological transition and sporulation of Bacillus thuringiensis in mixed cultures, whereas abrogation of the DSF synthase RpfF reduced the interference. DSF inhibited B. thuringiensis cell division and sporulation through modulation of ftsZ , which encodes an important cell division protein in bacterial cells. In addition, RpfF is essential for production of six DSF‐family signals in Xcc , which employ the same signaling pathways to regulate biological functions in Xcc and play similar effects on reduction of cell division, sporulation and antibiotic resistance of B. thuringiensis . Furthermore, abrogation of RpfF decreased the competitive capability of Xcc against B. thuringiensis on the surface of Chinese cabbage leaves. Our findings provide new insights into the role of DSF‐family signals in interspecies competition and depict molecular mechanisms with which Xcc competes with B. thuringiensis .

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Identification and characterization of naturally occurring DSF ‐family quorum sensing signal turnover system in the phytopathogen X anthomonas - Lian Zhou; Xing‐Yu Wang; Shuang Sun; Li‐Chao Yang; Bo‐Le Jiang; Ya‐Wen He (Environmental Microbiology, 2015)
Summary Molecules of the diffusible signal factor ( DSF )‐family are a class of quorum sensing ( QS ) signals used by the phytopathogens X anthomonas . Studies during the last decade have outlined how X anthomonas cells enter the QS phase. However, information on the mechanism underlying its exit from the QS phase is limited. RpfB has recently been reported as a fatty acyl‐ CoA ligase ( FCL ) that activates a wide range of fatty acids to their CoA esters in vitro . Here, we establish an improved quantification assay for DSF ‐family signals using liquid chromatography‐mass spectrometry in X . campestris pv. campestris ( X cc ). We first demonstrated that RpfB represents a naturally occurring DSF ‐family signal turnover system . RpfB effectively turns over DSF ‐family signals DSF and BDSF in vivo . RpfB FCL enzymatic activity is required for DSF and BDSF turnover. Deletion of rpf B slightly increased X cc virulence in the C hinese radish and overexpression of rpf B significantly decreased virulence. We further showed that the expression of rpf B is growth phase‐dependent, and its expression is significantly enhanced when X cc cells enter the stationary phase. DSF regulates rpf B expression in a concentration‐dependent manner. rpf B expression is also negatively regulated by the DSF signalling components RpfC , RpfG and C lp. The global transcription factor C lp directly binds to the AATGC ‐tgctgc‐ GCATC motif in the promoter region of rpf B to repress its expression. Finally, RpfB ‐dependent signal turnover system was detected in a wide range of bacterial species, suggesting that it is a conserved mechanism.

Changes in global DNA methylation intensity and DNMT1 transcription during the aging process of scallop Chlamys farreri - Shanshan Lian; Yan He; Xue Li; Bosong Zhao; Rui Hou; Xiaoli Hu; Lingling Zhang; Zhenmin Bao (Journal of Ocean University of China, 2015)

Association between PPAR-γ2 Pro12Ala polymorphism and obesity: a meta-analysis - Ying-shui Yao; Jie Li; Yue-long Jin; Yan Chen; Lian-ping He (Molecular Biology Reports, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

Petrogenesis of mid-Carboniferous volcanics and granitic intrusions from western Junggar Basin boreholes: geodynamic implications for the Central Asian Orogenic Belt in Northwest China - Di Li; Dengfa He; Yanhui Yang; Yichi Lian (International Geology Review, 2014)

A phylogenetic analysis of the ubiquitin superfamily based on sequence and structural information - Zhen Yang; Haikui Chen; Xiaobo Yang; Xueshuai Wan; Lian He; Ruoyu Miao; Huayu Yang; Yang Zhong; Li Wang; Haitao Zhao (Molecular Biology Reports, 2014)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

A new convenient technique for making cell blocks - Qing-Lian He; Ya-Zhen Zhu; Guang-Juan Zheng; Ling-Chun Shi; Shao-Wei Hu; Chu-Tian Li (Cell and Tissue Research, 2012)

The role and clinical implications of microRNAs in hepatocellular carcinoma - Xue Zhao; Zhen Yang; GuangBing Li; DongKai Li; Yi Zhao; Yan Wu; Simon C. Robson; Lian He; YiYao Xu; RuoYu Miao; HaiTao Zhao (Science China Life Sciences, 2012)
Hepatocellular carcinoma (HCC) is common and one of the most aggressive of all human cancers. Recent studies have indicated that miRNAs, a class of small noncoding RNAs that regulate gene expression post-transcriptionally, directly contribute to HCC by targeting many critical regulatory genes. Several miRNAs are involved in hepatitis B or hepatitis C virus replication and virus-induced changes, whereas others participate in multiple intracellular signaling pathways that modulate apoptosis, cell cycle checkpoints, and growth-factor-stimulated responses. When disturbed, these pathways appear to result in malignant transformation and ultimately HCC development. Recently, miRNAs circulating in the blood have acted as possible early diagnostic markers for HCC. These miRNA also could serve as indicators with respect to drug efficacy and be prognostic in HCC patients. Such biomarkers would assist stratification of HCC patients and help direct personalized therapy. Here, we summarize recent advances regarding the role of miRNAs in HCC development and progression. Our expectation is that these and ongoing studies will contribute to the understanding of the multiple roles of these small noncoding RNAs in liver tumorigenesis.

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Fetal exposure to bisphenol A affects the primordial follicle formation by inhibiting the meiotic progression of oocytes - Han-Qiong Zhang; Xi-Feng Zhang; Lian-Jun Zhang; Hu-He Chao; Bo Pan; Yan-Min Feng; Lan Li; Xiao-Feng Sun; Wei Shen (Molecular Biology Reports, 2012)

Bisphenol A exposure modifies methylation of imprinted genes in mouse oocytes via the estrogen receptor signaling pathway - Hu-He Chao; Xi-Feng Zhang; Bo Chen; Bo Pan; Lian-Jun Zhang; Lan Li; Xiao-Feng Sun; Qing-Hua Shi; Wei Shen (Histochemistry and Cell Biology, 2012)

Gene Expression Profiles in Response to Salt Stress in Hibiscus Tiliaceus - Guili Yang; Renchao Zhou; Tian Tang; Xiaoshu Chen; Jianhua Ouyang; Lian He; Weijin Li; Sufang Chen; Miaomiao Guo; Xinnian Li; Cairong Zhong; Suhua Shi (Plant Molecular Biology Reporter, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Cloning and characterization of HsfA2 from Lily (Lilium longiflorum) - Haibo Xin; Hua Zhang; Li Chen; Xiaoxin Li; Qinglong Lian; Xue Yuan; Xiaoyan Hu; Li Cao; Xiuli He; Mingfang Yi (Plant Cell Reports, 2010)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Enhanced 2,3-butanediol production by altering the mixed acid fermentation pathway in Klebsiella oxytoca - Xiao-Jun Ji; He Huang; Shuang Li; Jun Du; Min Lian (Biotechnology Letters, 2008)

Remediation of pentachlorophenol-contaminated soil by composting with immobilized Phanerochaete chrysosporium - Xiao-yun Jiang; Guang-ming Zeng; Dan-lian Huang; Yang Chen; Fang Liu; Guo-he Huang; Jian-bing Li; Bei-dou Xi; Hong-liang Liu (World Journal of Microbiology and Biotechnology, 2006)

Laccase activities of a soil fungus Penicillium simplicissimum in relation to lignin degradation - Guang Ming Zeng; Hong Yan Yu; Hong Li Huang; Dan Lian Huang; Yao Ning Chen; Guo He Huang; Jian Bing Li (World Journal of Microbiology and Biotechnology, 2006)

Body surface Laplacian mapping of atrial depolarization in healthy human subjects - J. Lian; G. Li; J. Cheng; B. Avitall; B. He (Medical & Biological Engineering & Computing, 2002)